Quality of endoscopic surveillance of Lynch syndrome patients in a Swedish cohort - Walton Bernstedt, Sophie; Haxhijaj, Adrianna; Jamizadeh, Nigin; Björk, Jan; Andreasson, Anna; Forsberg, Anna M; Backman, Ann-Sofie (Endoscopy International Open, 2024)
Background and study aims Risk factors for colorectal cancer (CRC) in Lynch syndrome (LS) include sex, age, smoking, high body mass index (BMI), surveillance interval length, and risk genotype. The Boston Bowel Preparation Scale (BBPS) produces a standardized bowel cleanliness rating. A low BBPS score might be a risk factor for missed early lesions. The aim of this study was to investigate the correlation between BBPS score and adenoma detection (with known risk factors for CRC) and surveillance interval with CRC detection in LS patients.Methods A retrospective cohort study including 366 LS patients with 1,887 colonoscopies under surveillance in Stockholm, Sweden from 1989 to 2021 was conducted. Associations were tested using linear and logistic regression.Results We found no association between BBPS score and number of adenomas detected. A low BBPS score was found to be associated with older age (regression coefficient (coeff) –0.015; 95% confidence interval [CI] –0.026 to –0.004; P = 0.007) and obesity (coeff = –0.48; 95% CI: –0.89 to –0.062; P = 0.024). A higher number of detected adenomas was associated with older age (coeff = 0.008; 95% CI 0.004 to 0.012; P < 0.001), male sex (coeff = 0.097; 95% CI 0.008 to 0.19; P = 0.033) and CRC (coeff = 0.28; 95% CI 0.061 to 0.50; P = 0.012). Surveillance interval length was not significant in CRC detection.Conclusions Bowel cleanliness was not associated with adenoma detection and was less likely achieved in patients who were older and had higher BMI. Adenoma detection was associated with older age and male sex. The results indicate the need for better adherence to guidelines and attention to older age groups, men, and patients with obesity.
Keywords: Endoscopy Lower GI Tract; Polyps / adenomas / ...; Colorectal cancer; Quality and logistical aspects